2019
DOI: 10.3389/fphar.2019.01400
|View full text |Cite|
|
Sign up to set email alerts
|

The Fruits of Siraitia grosvenorii: A Review of a Chinese Food-Medicine

Abstract: Siraitia grosvenorii (Swingle) C. Jeffrey, a member of the family Cucurbitaceae, is a unique economic and medicinal plant grown in China. For more than 300 years, S. grosvenorii has been used as a natural sweetener and as a traditional medicine for the treatment of pharyngitis, pharyngeal pain, as well as an anti-tussive remedy in China. It is one of the first approved medicine food homology species in China. It has been widely studied as a natural product with high development potential. Therefore, the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 79 publications
(23 reference statements)
0
55
0
1
Order By: Relevance
“…Mogroside V (MV) is the most abundant form of triterpenoid compound isolated from Siraitia grosvenorii (Swingle) C.Jeffrey ex A.M.Lu & Zhi Y.Zhang ( Liu H et al, 2018 ; Gong et al, 2019 ). Numerous studies have demonstrated that MV possesses broad pharmacological characteristics and properties, including antioxidant, anti-tussive, immunoregulatory, and anti-inflammatory effects ( Di et al, 2011 ; Itkin et al, 2016 ; Liu C et al, 2018 ).…”
Section: Natural Antioxidant-based Interventions To Reduce Oxidative mentioning
confidence: 99%
“…Mogroside V (MV) is the most abundant form of triterpenoid compound isolated from Siraitia grosvenorii (Swingle) C.Jeffrey ex A.M.Lu & Zhi Y.Zhang ( Liu H et al, 2018 ; Gong et al, 2019 ). Numerous studies have demonstrated that MV possesses broad pharmacological characteristics and properties, including antioxidant, anti-tussive, immunoregulatory, and anti-inflammatory effects ( Di et al, 2011 ; Itkin et al, 2016 ; Liu C et al, 2018 ).…”
Section: Natural Antioxidant-based Interventions To Reduce Oxidative mentioning
confidence: 99%
“…Furthermore, this fruit has been used as a natural sweetener [ 206 ] and as a traditional medicine for the treatment of pharyngitis, pharyngeal pain, cough, cold, sore throat, constipation, and dire thirst in China [ 207 , 208 ]. Mogroside in monk fruit has shown beneficial health effects against diabetes, malignant tumor, and inflammation in animal models [ 209 , 210 ] and could be used as a low-calorie sweetener for diabetic patients [ 206 ].…”
Section: Recent Trends In the Use Of Natural Sweeteners For Sugar mentioning
confidence: 99%
“…Siraitia grosvenorii (Swingle) C.Jeffrey ex A.M.Lu & Zhi Y.Zhang, also referred to as Momordica grosvenorii or Thladiantha grosvenorii, is a perennial vine of the Cucurbitaceae family (Pawar, Krynitsky, & Rader, 2016). Commonly known as "monk fruit" or "luo han guo", S. grosvenorii is native to the southern part of China, where it has been used as a food ingredient and herbal medicine for more than 300 years (Gong et al, 2019;Soejarto, Addo, & Kinghorn, 2019). S. grosvenorii is applied in typical ethnomedical treatments of ailments such as coughs, lung congestion, and sore throats and was one of the first food homology species approved for medical use in China (Gong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%